Design Science in Digital Innovation: A Literature Review - Horita, Flávio; Rocha, Fabio; Souza, Layse; Gonzales, Gustavo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de Informação, 2020)
Digital innovation focuses on using digital technologies to orchestrate new products, services, platforms, or even new business models in a given context. Design science research has the potential to contribute to digital innovation as it focuses on the development of innovative IT artifacts. However, existing literature still lacks an understanding of how these two disciplines would converge. This article conducts a literature review that examines this issue intending to obtain an overview of the current state of the art, which leads to a research agenda.We employ a systematic approach to mapping in first-line journals, and well-known IS conferences. The results of the study revealed that most studies are focused on providing two types of contributions (Model and Method). They also showed, as well as the need to employ design science for developing innovative artifacts in new emerging application domains such as disaster management or urban mobility.